If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -5) = 122 Reorder the terms: x(-5 + 2x) = 122 (-5 * x + 2x * x) = 122 (-5x + 2x2) = 122 Solving -5x + 2x2 = 122 Solving for variable 'x'. Reorder the terms: -122 + -5x + 2x2 = 122 + -122 Combine like terms: 122 + -122 = 0 -122 + -5x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -61 + -2.5x + x2 = 0 Move the constant term to the right: Add '61' to each side of the equation. -61 + -2.5x + 61 + x2 = 0 + 61 Reorder the terms: -61 + 61 + -2.5x + x2 = 0 + 61 Combine like terms: -61 + 61 = 0 0 + -2.5x + x2 = 0 + 61 -2.5x + x2 = 0 + 61 Combine like terms: 0 + 61 = 61 -2.5x + x2 = 61 The x term is -2.5x. Take half its coefficient (-1.25). Square it (1.5625) and add it to both sides. Add '1.5625' to each side of the equation. -2.5x + 1.5625 + x2 = 61 + 1.5625 Reorder the terms: 1.5625 + -2.5x + x2 = 61 + 1.5625 Combine like terms: 61 + 1.5625 = 62.5625 1.5625 + -2.5x + x2 = 62.5625 Factor a perfect square on the left side: (x + -1.25)(x + -1.25) = 62.5625 Calculate the square root of the right side: 7.90964601 Break this problem into two subproblems by setting (x + -1.25) equal to 7.90964601 and -7.90964601.Subproblem 1
x + -1.25 = 7.90964601 Simplifying x + -1.25 = 7.90964601 Reorder the terms: -1.25 + x = 7.90964601 Solving -1.25 + x = 7.90964601 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.25' to each side of the equation. -1.25 + 1.25 + x = 7.90964601 + 1.25 Combine like terms: -1.25 + 1.25 = 0.00 0.00 + x = 7.90964601 + 1.25 x = 7.90964601 + 1.25 Combine like terms: 7.90964601 + 1.25 = 9.15964601 x = 9.15964601 Simplifying x = 9.15964601Subproblem 2
x + -1.25 = -7.90964601 Simplifying x + -1.25 = -7.90964601 Reorder the terms: -1.25 + x = -7.90964601 Solving -1.25 + x = -7.90964601 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.25' to each side of the equation. -1.25 + 1.25 + x = -7.90964601 + 1.25 Combine like terms: -1.25 + 1.25 = 0.00 0.00 + x = -7.90964601 + 1.25 x = -7.90964601 + 1.25 Combine like terms: -7.90964601 + 1.25 = -6.65964601 x = -6.65964601 Simplifying x = -6.65964601Solution
The solution to the problem is based on the solutions from the subproblems. x = {9.15964601, -6.65964601}
| 9x-y=-13 | | a+(9+4)=(a+5)-(a+1) | | 6y+4-3y=10+2y+8 | | 3e=-33 | | 11d+d-4d=8 | | -9x+4y-7x=(x-97+y) | | 8s-17=39+s | | 3*4+5x= | | 7+(-1)+12-7= | | -9+4y-7x=(x-97+y) | | 9+7y-y=51 | | 5-8y+11y=13-3 | | 4w=2w+6 | | 4n+20=6n | | 3t+5t-7=9 | | 9xy+6x^2y^3=0 | | 3b+b-6=-18 | | 54=-6f | | 9(y+10)+y=3(y+3)+4 | | 15+7y-y=51 | | x+7+3(4+5)=(x*12)+12 | | 2x^5-11x^4+10x^3+8x=0 | | X+34=12x+12 | | 10-7x-7-8x=6 | | 2xy+6x-y-17=0 | | -5(t-2)+9t=7t-9 | | 9x+2=9(x-3) | | 4x+2x+4=10 | | 5(3x-3)=15x-15 | | -2-3r=10 | | 7x+3=-4+3x+23 | | 6x+3=(4-2) |